THE RELATIONSHIP OF THE VERTICAL STRENGTH OF THE STAGE OF ELEVATION OF THE SCORING BY JUMPING WITH THE LEVEL OF ACHIEVEMENT OF THE BASKETBALL PLAYERS - Assist Prof. Dr.Muataz Khleel Ibrahim (Galaxy International Interdisciplinary Research Journal, 2023)
The first chapter dealt with the basketball game because of its great importance, as it is played by all the age stages, which depend on multiple mechanical foundations and kinematic and kinetic variables. And an impact on the level of achievement, as its sections are interconnected through its performance with high strength and speed within a very short period of time, and in the second chapter, the researcher used the descriptive approach in the manner of survey studies to suit the nature of the research. The total population sample consisted of (10) players. A player from Al-Zawraa Basketball Club for the season (2018-2019), the researcher used digital photography to achieve the scientific and technical observation, using a digital imaging camera type (yashica) at a speed of (400 images / s) number (2), the first is placed on the right side and the second is from The left side, at a distance of (5 meters) from the scoring area, with a height of (130 cm) to identify the biomechanical variables related to the skill of scoring by jumping with basketball, and a force measuring platform was used. It has the ability to measure the force. As for the third chapter, the results were reached through the existence of a negative significant correlation between the lowest reaction force in the action stage and the achievement, as the calculated (r) value reached (-0.92), and the researcher attributes that the lowest reaction force in the action stage is in part of the action stage as a whole. What is correct is that the lowest reaction force in the action phase leads to a decrease in the force recorded in the propulsion phase because the significant decrease in force means the length of the absorption time, which leads to a loss in the force transferred from the impulse phase to the action phase, which negatively affects the achievement. This is confirmed by the area under the curve, which expresses the recorded force.